Medical and economic burden of influenza in the elderly population in central and eastern European countries - Kovács, Gábor; Kaló, Zoltán; Jahnz-Rozyk, Karina; Kyncl, Jan; Csohan, Agnes; Pistol, Adriana; Leleka, Mariya; Kipshakbaev, Rafail; Durand, Laure; Macabeo, Bérengère (Human vaccines & immunotherapeutics, 2014)
Influenza affects 5-15% of the population during an epidemic. In Western Europe, vaccination of at-risk groups forms the cornerstone of influenza prevention. However, vaccination coverage of the elderly (> 65 y) is often low in Central and Eastern Europe (CEE); potentially because a paucity of country-specific data limits evidence-based policy making. Therefore the medical and economic burden of influenza were estimated in elderly populations in the Czech Republic, Hungary, Kazakhstan, Poland, Romania, and Ukraine. Data covering national influenza vaccination policies, surveillance and reporting, healthcare costs, populations, and epidemiology were obtained via literature review, open-access websites and databases, and interviews with experts. A simplified model of patient treatment flow incorporating cost, population, and incidence/prevalence data was used to calculate the influenza burden per country. In the elderly, influenza represented a large burden on the assessed healthcare systems, with yearly excess hospitalization rates of ~30/100,000. Burden varied between countries and was likely influenced by population size, surveillance system, healthcare provision, and vaccine coverage. The greatest burden was found in Poland, where direct costs were over EUR 5 million. Substantial differences in data availability and quality were identified, and to fully quantify the burden of influenza in CEE, influenza reporting systems should be standardized. This study most probably underestimates the real burden of influenza, however the public health problem is recognized worldwide, and will further increase with population aging. Extending influenza vaccination of the elderly may be a cost-effective way to reduce the burden of influenza in CEE.
Keywords: elderly; Influenza, Human; Europe; Influenza Vaccines; Prevalence; vaccination; náklady na zdravotní péči; vakcinace; lidé; cost of illness; Evropa; public health; Aged, 80 and over; Incidence; prevalence; Vaccination; vakcíny proti chřipce; Male; incidence; Aged; health care system; influenza; chřipka lidská; senioři nad 80 let; senioři; mužské pohlaví; Health Care Costs; Humans